2004
DOI: 10.4049/jimmunol.173.2.1276
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Farnesyltransferase Prevents Collagen-Induced Arthritis by Down-Regulation of Inflammatory Gene Expression through Suppression of p21ras-Dependent NF-κB Activation

Abstract: Farnesylation of p21ras is an important step in the intracellular signaling pathway of growth factors, hormones, and immune stimulants. We synthesized a potent and selective farnesyltransferase inhibitor (LB42708) with IC50 values of 0.8 nM in vitro and 8 nM in cultured cells against p21ras farnesylation and examined the effects of this inhibitor in the settings of inflammation and arthritis. LB42708 suppressed NF-κB activation and iNOS promoter activity by suppressing the I-κB kinase activity and I-κBα degrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 44 publications
3
36
3
Order By: Relevance
“…The functional dimers migrate to the nucleus and ligate specific transcriptional response elements. FTIs inhibit NF-B in cells other than RASFs by acting on farnesylated proteins upstream of IKK (39,40). NF-B has been implicated in regulating 2850 ABELES ET AL MMP-1 secretion (15,71,72), and our results suggest that one or more farnesylated proteins regulate the levels of MMP-1 via effects on NF-B.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…The functional dimers migrate to the nucleus and ligate specific transcriptional response elements. FTIs inhibit NF-B in cells other than RASFs by acting on farnesylated proteins upstream of IKK (39,40). NF-B has been implicated in regulating 2850 ABELES ET AL MMP-1 secretion (15,71,72), and our results suggest that one or more farnesylated proteins regulate the levels of MMP-1 via effects on NF-B.…”
Section: Discussionsupporting
confidence: 49%
“…Alternatively, protein farnesylation and geranylgeranylation can be specifically blocked by inhibitors of these enzymes. FT inhibitors (FTIs), currently being used in phase III trials for neoplastic disease, were originally designed as chemotherapeutic inhibitors of Ras (37,38), but have also been reported to have antiinflammatory properties both in vitro and in vivo (39,40). FTIs inhibit both MAPK and NF-B in macrophages (39,41), and were beneficial in a mouse model of arthritis (39).…”
Section: Results Fti-276 But Not Statins Inhibited Rasf Secretion mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown the role of Ras in different inflammatory processes. 25,33 The anti-inflammatory effects of FTIs are important in several diseases, including collagen-induced arthritis 34 and atherosclerosis. 35 In addition, FTIs have been shown to inhibit corneal inflammation by inhibiting macrophage function and decreasing their survival.…”
Section: Discussionmentioning
confidence: 99%
“…Cells were incubated with serum-free medium for 4 h and nuclear extracts were prepared as described (Na et al, 2004). A double-stranded AP-1-specific probe (5'-CGCTTGATGAGTCAGCCGGAA-3'; the AP-1 recognition sequence is underlined) was labeled with [γ-32 P]ATP using T4 polynucleotide kinase and purified on a G-50 Sephadex column.…”
Section: Electrophoretic M Obility Shift Assay (Em Sa )mentioning
confidence: 99%